Consumers' Perceptions of Deal Presentations for Green Products. Issue 4 (November 2022) - Tripathi, Avinash; Pandey, Neeraj
There is no clarity on when and why consumers prefer specific sales promotions for the green versus non-green products. This research conducts a comparative analysis through three experiments to provide a theoretical explanation. It enhances the understanding of the impact of bonus pack versus price discount promotions for different characteristics, varying purchase volume, and the effect of information on buyers' choices. The results show that buyers do not prefer price discounts when purchasing low-involvement green products, and they do not prefer bonus packs when purchasing low-involvement non-green products. Remarkably, for high-involvement products, the buyers prefer bonus packs when purchasing green products; however, they show no specific inclination while purchasing non-green products. These effects are further influenced by emphasizing deal-savings and varying purchase volume. In addition, this research explains the reason for consumers' deal preferences through identifying the mediating role of the anticipated regret and conditional indirect effect of perceived expertise. The findings have significant practical implications.